2020
DOI: 10.1371/journal.pone.0240179
|View full text |Cite
|
Sign up to set email alerts
|

Seeing through the forest: The gaze path to purchase

Abstract: Eye tracking studies have analyzed the relationship between visual attention to point of purchase marketing elements (price, signage, etc.) and purchase intention. Our study is the first to investigate the relationship between the gaze sequence in which consumers view a display (including gaze aversion away from products) and the influence of consumer (top down) characteristics on product choice. We conducted an in-lab 3 (display size: large, moderate, small) X 2 (price: sale, non-sale) within-subject experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 67 publications
1
6
0
Order By: Relevance
“…selected in this study, including total duration of fixations (TDF), number of fixations (NF), average duration of fixations (ADF), average pupil size (APS) and average amplitude of saccades (AAS). Among them, total duration of fixations and number of fixations can be regarded as a measure of attractiveness [72,73] and can reflect the visual preference of participants [74].…”
Section: Plos Onementioning
confidence: 99%
“…selected in this study, including total duration of fixations (TDF), number of fixations (NF), average duration of fixations (ADF), average pupil size (APS) and average amplitude of saccades (AAS). Among them, total duration of fixations and number of fixations can be regarded as a measure of attractiveness [72,73] and can reflect the visual preference of participants [74].…”
Section: Plos Onementioning
confidence: 99%
“…On the other hand, having too many discrete visual cues may not lead to greater support for crowdfunding products. Gaze-aversion literature finds that a multitude of discrete visual cues can be overwhelming, so to alleviate their discomfort, consumers may seek to avoid images with too many discrete visual elements and decrease their purchases [55]. That is, having too many discrete visual elements may lead to images being ignored and eventually reduce comprehensibility [17].…”
Section: Number Of Facesmentioning
confidence: 99%
“…Typically, the elements in the landscape are established to specific Areas of Interest (AOI), and the eye-tracking data in these AOIs are analyzed in more detail and calculated (Huang and Lin, 2020). Studies have shown that the total duration of fixation and fixation count of stimulus materials are considered to be attractive judgments (Behe et al, 2015(Behe et al, , 2020, and the fixation count significantly positively correlates with the subjective preference rating (Zheng et al, 2021). In poor restorative environments, eye movements fixate more frequently for shorter durations (Martínez-Soto et al, 2019).…”
Section: Introductionmentioning
confidence: 99%